Trade Union Approaches towards the ICE Regulations: Defensive Realism or Missed Opportunity?. (8th August 2013) - Hall, Mark; Purcell, John; Terry, Michael; Hutchinson, Sue; Parker, Jane
Abstract Reflecting debates about whether statutory workforce‐wide consultation arrangements are likely to undermine or underpin trade union representation, unions' approaches towards the UK's Information and Consultation of Employees Regulations 2004 have been ambivalent and their engagement with the legislation limited. Evidence from longitudinal case studies in 25 organizations suggests that the introduction of information and consultation bodies did not have the effect of marginalizing trade union representation and collective bargaining, and in some cases reinforced unions' standing within the organization. The article highlights the implications for union strategies and legislative reform, and suggests a research agenda.